Wireless Universal Power Plug For Load - Hui, Tan Chun; Zainal Abidin, Zuhairiah (Evolution in Electrical and Electronic Engineering, 2020)
Wireless concept is a type of power transfer between two objects that are not connected by the wire and it is the simplest way to eliminate the use of copper wire. The traditional power plug has brought some limitation such as use of conventional copper cable and current carrying wire that will leads some power loss and inconvenient for users. The main objective of the project is to design a wireless universal power plug for load and scope of the project is focus on the near field wireless power transfer. Transmitter circuit and receiver circuit are designed for wireless universal power plug. As the results, the relaxation oscillator circuit produced high AC power and frequency almost 180 kHz while full bridge rectifier circuit produced DC power and 5 V output voltage. When the distance between transmitter coil and receiver coil is increased, the performances of the system are decreased. In conclusion, the innovation for the wireless universal power plug will increase the efficiency of power transmission since reduces the power loss due to wire. Higher number of turns of copper wire can be used for future work so that the power can be transmitted in longer distance.